2017
DOI: 10.1111/jfs.12416
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo characterization of the antibacterial activity and membrane damage mechanism of quinic acid against Staphylococcus aureus

Abstract: In this study, we investigated the antibacterial activity of quinic acid (QA) and elucidated its membrane action mechanism against Staphylococcus aureus. In vitro antibacterial assay showed that QA effectively inhibited the growth of test bacteria. In model food systems of cabbage suspension and barley soup, QA possessed a great antibacterial capacity. The membrane hyperpolarization and a decrease of membrane fluidity demonstrated a significant effect of QA on damaging the normal functions of cell membrane, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 33 publications
2
22
0
Order By: Relevance
“…The food model medium tested in this study was barley soup (pH 6.5). It was used to evaluate the antibacterial activity of SCE by previously published methods (Bai et al ) with some modifications. In brief, barley soup was prepared by adding barley powder to distilled water (5% wt/vol).…”
Section: Methodsmentioning
confidence: 99%
“…The food model medium tested in this study was barley soup (pH 6.5). It was used to evaluate the antibacterial activity of SCE by previously published methods (Bai et al ) with some modifications. In brief, barley soup was prepared by adding barley powder to distilled water (5% wt/vol).…”
Section: Methodsmentioning
confidence: 99%
“…The antibacterial activity in food systems experiments were carried out as previously reported with minor modifications 13 . Briefly, cabbage suspension consists of squeezing cabbage juice and aseptic distilled water (50% vol/vol).…”
Section: Methodsmentioning
confidence: 99%
“…In order to provide a theoretical basis of the further application of VYE and DMY in food, the antibacterial mechanism of VTE and DMY against Staphylococcus aureus were systematically evaluated in this study, including Antibacterial activity in food systems. The antibacterial activity in food systems experiments were carried out as previously reported with minor modifications 13 . Briefly, cabbage suspension consists of squeezing cabbage juice and aseptic distilled water (50% vol/vol).…”
mentioning
confidence: 99%
“…Quinic acid also has strong antibacterial properties where it can easily attack the intracellular cell of bacteria. Quinic acid has the ability to reduce the succinate dehydrogenase activity and DNA content of bacteria (Bai et al, 2018). Studies by Slobodníková et al (2016) demonstrated tannic acid which represents one of the most common polyphenols, possess antibacterial against both Gram-positive and Gram-negative bacteria by penetrating the lipid bilayers and damaging their membrane.…”
Section: Presence Of Phenolic Constituent In Sugarcane Molasses Extractmentioning
confidence: 99%